Bilateral cytomegalovirus retinitis as the presenting feature of Dyskeratosis Congenita. Issue 3 (May 2023) - Arora, Atul; Singh, Ramandeep; Dogra, Mohit
Purpose: To describe a young male with bilateral sequential Cytomegalovirus retinitis (CMVR) as the presenting feature of Dyskeratosis Congenita Case report: A 25-year-old human immunodeficiency virus (HIV) negative male developed CMVR in his left eye, while on a three week course of oral valganciclovir therapy for CMV retinitis in his right eye. Systemic examination revealed reticular hypopigmentation of the forearms, dystrophic nails, oral leukoplakia and complete blood counts showed pancytopenia. A diagnosis of Dyskeratosis Congenita was confirmed with genetic testing. Conclusion: CMVR in non-HIV individuals should be considered as a harbinger of systemic immunosuppressive conditions. Ophthalmologists may be the first ones to suspect and diagnose congenital immunosuppressive disorders like Dyskeratosis Congenita in these patients.